Smoothed particle hydrodynamics simulation for injection molding flow of short fiber-reinforced polymer composites - He, L.; Lu, G.; Chen, D.; Li, W.; Chen, L.; Yuan, J.; Lu, Chunsheng (Sage Publications, 2017)
The injection molding process of short fiber-reinforced polymer composites was investigated using smoothed particle hydrodynamics method. The polymer melt was modeled as a power law fluid, and the fibers were considered as rigid bodies. The flow behavior of short fiber-reinforced polymer composite melt and the motion and orientation of fibers were studied. The results showed that U-shaped fountain flow was generated at the flow front, and the center of the flow front gradually sank during the injection molding process; fibers were aligned to the flow direction in the cavity and near the wall in the sprue, and fibers accumulated at some points in the cavity. Additionally, the initial fiber configuration in the model influenced the final fiber orientation slightly. It was also found that the fiber orientation factor increased with the increase of fiber aspect ratio, and decreased with the increase of fiber content.